2022
DOI: 10.1186/s12933-022-01613-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of glucokinase activation on risk of cardiovascular disease: a Mendelian randomisation analysis

Abstract: Background Glucokinase activators (GKAs) are an emerging class of glucose lowering drugs that activate the glucose-sensing enzyme glucokinase (GK). Pending formal cardiovascular outcome trials, we applied two-sample Mendelian randomisation (MR) to investigate the impact of GK activation on risk of cardiovascular diseases. Methods We used independent genetic variants in or around the glucokinase gene meanwhile associated with HbA1c at genome-wide si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
(47 reference statements)
1
4
0
Order By: Relevance
“…We also evaluated impacts of GK activation on these outcomes using GCK SNPs associated with FPG as IVs. The results were overall consistent with our previous analysis using GCK SNPs associated with HbA1c as IVs [ 26 ]. In contrast to the impaired GK-GKRP interaction, GK activation did not influence the lipid traits.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We also evaluated impacts of GK activation on these outcomes using GCK SNPs associated with FPG as IVs. The results were overall consistent with our previous analysis using GCK SNPs associated with HbA1c as IVs [ 26 ]. In contrast to the impaired GK-GKRP interaction, GK activation did not influence the lipid traits.…”
Section: Discussionsupporting
confidence: 91%
“…In 2022, the first GKA (dorzagliatin) had been approved for treatment of T2D in China and so far, no data (more than 52 weeks) are available on its long-term effects. A previous MR study investigated the impact of GK activation (instrumented by GCK SNPs associated with HbA1c) on cardiovascular outcomes, suggesting its possible protective effects against CAD and HF [ 26 ]. However, it should be noted that some GKAs have been associated with dyslipidaemia, notably hypertriglyceridemia [ 16 ] although this was not reported with Dorzagliatin [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…55,60 The second point is that, unlike some antidiabetic drugs such as SGLT-2 inhibitors or GLP-1 receptor agonists, which have been demonstrated to have special mechanisms to improve cardiovascular outcomes, GK activators build their efficacy directly on the recovery of GK target to achieve ideal glucose control, which may have stronger protective effects on coronary artery disease and heart failure than nontargeted glucose-lowering regimens. 61 Because impaired glucose homeostasis occurs at a very early stage of diabetes, studies with a larger population of patients with diabetes and prediabetes will add more clinical evidence to the long-term benefits of GK activation.…”
Section: Perspectivementioning
confidence: 99%
“…Indeed, some of the loci associated with type 2 diabetes lie within the coding or non-coding regions of MODY genes [24,25,86] . One example is the common variants of GCK and GCK-regulating proteins associated with glucose/lipid traits and ESKD [87] . Mendelian randomization analysis suggested that genetic proxies of GCK were causally linked to cardiovascular disease [88] .…”
Section: Glucokinase Modymentioning
confidence: 99%